The Performance of Manufacturing Companies in Indonesia is Reviewed From The Characteristics of The Board of Directors, Audit Committee and Ownership - Yanto, Wedi; Juliani, Meily; Candra, Rudi (Accounting Department, Faculty of Business and Management, Universitas Internasional Batam, 2023)
Purpose - This research aims to prove the influence of the characteristics of the board of directors, audit committee, and ownership on the performance of manufacturing companies in Indonesia. Research Method - Manufacturing companies that are registered on the IDX are used as objects in this research using a purposive sampling method and were obtained from 124 manufacturing companies in 2018-2022. Testing and analysis used Eviews 12 and IBM SPSS Statistics 25 software. Findings - The results of this study are ownership concentration which has a significant positive effect and independent audit committee, independent board of directors have a significant negative effect on company performance. The results of this research are that ownership concentration has a significant positive effect on company performance. Independent audit committees and independent boards of directors have a significant negative effect on company performance. Meanwhile, other variables do not have a significant effect on company performance. Implication - GCG can help companies create effective policies. It also can help companies build the trust of stakeholders and shareholders.